Development and characterization of agglomerated abrasives based on agro-industrial by-products. Issue 1 (31st December 2023) - Defo, Narcisse; Sikame, Rodrigue Nicodème Tagne; Huisken, William Paul Mejouyo; Ndapeu, Dieunedort; Tido, Stanislas Tiwa; Bistac-Brogly, Sophie; Njeugna, Ebenezer
ABSTRACT: The present work deals with the valorization of agro-industrial by-products to realize bonded abrasives. Four by-products were studied because of their wide availability and mechanical properties: palm nuts shells ( Elaeis guineensis ), Coco Nucifera shells, fruit kernels of Canarium schweinfurthii and fruit kernels of Raffia Vinifera . The Oliver and Pharr hardness and Young's modulus of the raffia cores are obtained by instrumented macro indentation, giving the values 101 MPa and 1.82 GPa, respectively. The development of the abrasive wheels was based on the experimental method of full factorial design at 2 levels. Porosity, hardness, resilience, material removal rate and wear were determined. Leeb 280 HL hardness shoe sole material was used for tribological testing. The optimal formulations have 20% binder content and 1 mm grain size of the four agro-industrial by-products used with a higher material removal rate and a longer life than commercial grinding wheels. These results presage their use in the shoe industry and abrasive disc huskers. GRAPHICAL ABSTRACT: uf0001